Effect of Epstein-Barr Virus Infection on the Treatment of Gastric Cancer in Tumor Immunotherapy - Xu , Tiancheng (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Gastric cancer is one of the biggest medical problems in the world today, and it is also a huge medical challenge for human beings. The main challenge is the complexity of the limitations of gastric cancer itself. At present, the efficacy of single-drug immune checkpoint inhibitors in treatment is not clear. It can be found in previous cases that Epstein-Barr virus positive gastric cancer patients have significantly higher response to PD-1 antibodies than the overall patients, from which it can be found that EBV infection can play an important role in gastric cancer immunotherapy. The purpose of this study was to investigate the effect of Epstein-Barr virus infection on gastric cancer and analyze specific clinical cases. The results showed that patients infected with Epstein-Barr virus had obvious advantages in the treatment of gastric cancer, which was significantly correlated with the expression of PD-L1 and EBV (+). This study highlights the potential benefits of Epstein-Barr virus infection in the treatment of gastric cancer, providing new insights into the development of future immunotherapy strategies. These findings will help to improve the treatment of gastric cancer patients, as well as to better understand the immune properties of gastric cancer and develop related vaccines. The significance of this study is that it provides a solid foundation for innovation in the treatment of gastric cancer.